The effects of shared book reading on the emotional vocabulary development of preschool children - Lindsay Dennis; Taryn Wade; Tai Cole; Danielle Morsching; Cassidy Haglund (Vocabulary Learning and Instruction)
Emotion vocabulary development is a skill that can be targeted in preschools using shared book reading. The purpose of this study was to examine the effects of a shared book reading intervention on the development of preschool children’s emotional vocabulary. Five typically developing 4-year-old children participated in the study. A single-case research design (SCRD) was employed; specifically, a multiple probe across behaviors. The primary dependent variable was the children’s ability to receptively identify emotion vocabulary depicted in Google images as well as provide correct responses to inference questions targeting emotion vocabulary. Results indicate that while all five children increased their ability to receptively identify emotion vocabulary and provide correct responses to questions targeting emotional vocabulary during instructional sessions, probe results were variable for both measures. Implications for research and practice are provided.